A Pilot Study Examining Patient Attitudes and Intentions to Adopt Assistive Technologies Into Type 2 Diabetes Self-Management. (26th November 2014) - Dobson, Kathleen G.; Hall, Peter
Background: Approximately half of individuals living with type 2 diabetes mellitus (T2DM) have suboptimal self-management, which could be improved by using assistive technologies in self-management regimes. This study examines patient attitudes and intentions to adopt assistive technologies into T2DM self-management. Methods: Forty-four participants ( M = 58.7 years) with T2DM were recruited from diabetes education classes in the southwestern Ontario, Canada, between February and April 2014. Participants completed a self-reported in-person survey assessing demographic characteristics, current diabetes management, and attitudes toward using assistive technologies in their diabetes self-management. Demographics, disease characteristics, and current technology use and preferences of the cohort were examined, followed by a correlational analysis of descriptive characteristics and attitudes and intentions to use technology in self-management. Results: The majority of (but not all) participants felt that using Internet applications (65%) and smartphone (53.5%) applications for self-management was a good idea. The majority of participants did not currently use an Internet (92.5%) or mobile (96%) application for self-management. Of participants, 77% intended to use an Internet application to manage their diabetes in the future and 58% intended to use mobile applications. Younger age was associated with more positive attitudes ( r = –.432, P = .003) and intentions ( r = –.425, P = .005) to use assistive technologies in diabetes self-management. Conclusions: Findings suggest that patients, especially those younger in age, are favorable toward adopting assistive technologies into management practice. However, attitudes among older adults are less positive, and few currently make use of such technologies in any age group.